Project Based Learning in Science Education Research in Indonesia: A Bibliometric Analysis - Permadi, Dimas; Antika, Rindi Novitri; Anggreini, Anggreini; Hilmalia, Yiksi; Yulandari, Atika (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
Project-based learning (PjBL) is increasingly recognised in science education in Indonesia as a strategy to improve students' higher order thinking skills and real-world problem solving. This article analyses the trends and patterns of PjBL research in Indonesia from 2020 to 2024 using a bibliometric approach. Research data were collected from Google Scholar, Crossref, and OpenAlex databases, then analysed descriptively qualitatively and visualised using VOSviewer. The results of the analysis showed that the majority of studies were experimental (68.36%), focusing on evaluating the effectiveness of PjBL in improving learning outcomes and critical thinking skills, particularly in the context of higher education and digital technology integration. The implementation of PjBL is considered effective in fostering students' creativity, motivation and 21st century competencies. However, there are still implementation challenges that require further study. Based on these findings, it is concluded that PjBL has great potential as a key approach in the Indonesian science curriculum. Therefore, further studies are needed to optimise its effectiveness and overcome the existing obstacles.